Experimental games for developing institutional capacity to manage common water infrastructure in India - Falk, Thomas; Kumar, S.; Srigiri, S. (Elsevier, 2019)
Since the 1990s, India invested more than one billion USD in participatory watershed development. Amongst other interventions, the rehabilitation of small-scale water harvesting infrastructure is a main focus. Nevertheless, despite its multiple economic and ecological benefits, many communities fail to maintain the structures. External support in this regard focuses largely on the promotion of blueprint solutions such as community water funds or organizational capacity development of Water User Associations. Little attention is paid to supporting the communities in developing rules related to the actual water and water infrastructure management. In this study we explored how experimental games closely framed to local conditions can help to better understand coordination challenges and develop institutional capacities related to managing small village reservoirs in Rajasthan/India. We played artefactual public good experiments with 300 water managers and combined the games with discussions. The approach created awareness for the cooperation challenges, facilitated debate related to possible solutions and helped to better understand cooperation patterns. Our results suggest that participants were playing substantially better than the predictions of standard economic theory but also substantially better than the behavior observed in real life. The discussions showed that the players connected the game to their real life experiences. They highlighted challenges but also gave examples where cooperation in the community is working well. The games allowed them to experiment in a compressed way with different institutions which deepened the discussion.